Office 4.0 – modern office digital technology, relevant to the post-COVID era - E. V. Vasilieva; O. I. Dolganova (Вестник университета)
The COVID-19 epidemic forced most employers to transfer employees to a remote format, and after the restrictions were lifted, many companies retained this regime. Therefore, an urgent topic today is the discussion of the question of whether the hybrid or online format will remain as established forms of interaction between people. The purpose of the study is to identify the main problems in corporate governance that arose during the forced transfer of some of the personnel to a remote work format and to show the possibilities of their solution based on digital tools. Coordination of work in a team affects not so much the productivity of each employee as the formation of a general vision of the situation, the quality of setting and solving problems, the presence of informal communications and the stability of horizontal ties, and the support and adaptation of new team members. To substantiate the choice of a hybrid office, expert assessments and the method of analysing hierarchies have been applied. The article provides a list of tools that ensure the operation of a hybrid office, formulates their advantages and development prospects. The possibility of assessing the effectiveness of such decisions using the total cost of ownership methodology on the example of introducing a biometrics system in a bank has been shown.